2015
DOI: 10.1088/0004-637x/806/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Cloud–cloud Collision as a Trigger of the High-Mass Star Formation: A Molecular Line Study in RCW 120

Abstract: RCW 120 is a Galactic H II region that has a beautiful ring shape that is bright in the infrared. Our new CO J = 1-0 and J = 3-2 observations performed with the NANTEN2, Mopra, and ASTE telescopes have revealed that two molecular clouds with a velocity separation of 20 km s −1 are both physically associated with RCW 120. The cloud at −8 km s −1 apparently traces the infrared ring, while the other cloud at −28 km s −1 is distributed just outside the opening of the infrared ring, interacting with the H II region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
170
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(192 citation statements)
references
References 69 publications
(156 reference statements)
21
170
1
Order By: Relevance
“…In fact, we note that this cloud shows similarities with the studied molecular clouds next to the Serpens cluster (Duarte-Cabral et al 2011) and RCW120 (Torii et al 2015), whose velocity components are thought to be caused by cloud-cloud collisions. Cloud-cloud collisions, studied using hydrodynamical simulations (Habe & Ohta 1992, Duarte-Cabral et al 2011,Takahira, Tasker & Habe 2014,Torii et al 2015, recently renewed popularity to explain the presence of high mass star-formation inside molecular clouds. Notably, such collisions between molecular clouds are thought to generate OB stars, filamentary clouds, dense cores and complex velocity distribution.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In fact, we note that this cloud shows similarities with the studied molecular clouds next to the Serpens cluster (Duarte-Cabral et al 2011) and RCW120 (Torii et al 2015), whose velocity components are thought to be caused by cloud-cloud collisions. Cloud-cloud collisions, studied using hydrodynamical simulations (Habe & Ohta 1992, Duarte-Cabral et al 2011,Takahira, Tasker & Habe 2014,Torii et al 2015, recently renewed popularity to explain the presence of high mass star-formation inside molecular clouds. Notably, such collisions between molecular clouds are thought to generate OB stars, filamentary clouds, dense cores and complex velocity distribution.…”
Section: Discussionmentioning
confidence: 53%
“…We also noted a dense region at (RA, Dec)=(18.421h, −13.282 • ) with mass MH 2 ∼ 1 × 10 5 M and H2 density nH 2 ∼ 7 × 10 2 cm −3 which showed enhanced turbulence. We indicated that its CS(1-0) and 13 CO(1-0) velocity structure, the presence of a UC Hii region and several OB stars and high mass star-forming regions, can be signatures of turbulent clouds caused by cloud cloud collisions (e.g RCW 120 Torii et al 2015). We also suggested that its possible interaction with P1's progenitor SNR was unlikely to cause such disruptions.…”
Section: Resultsmentioning
confidence: 85%
“…There are claims that CCC possibly drives the most of massive star formation within the Galaxy (c.f. Tan 2000;Nakamura et al 2012;Fukui et al 2014;Torii et al 2015;Fukui et al 2015bFukui et al , 2016. Therefore, the GMCMF time evolution may also be modified by CCC.…”
Section: Introductionmentioning
confidence: 99%
“…Some H  regions do show a central decrement in emission near the ionizing star (e.g., N49; Watson et al 2008) in these tracers, but others do not (e.g., RCW 120; Ochsendorf et al 2014b;Torii et al 2015). This can be understood if some SWBs fill only a small fraction of the H  region along the line of sight (so that the fractional decrement is small), but we then need more sensitive tracers to detect these SWBs.…”
Section: Introductionmentioning
confidence: 99%